LITERATURE REVIEW: KORELASI PENGETAHUAN TERHADAP KEPATUHAN PENGOBATAN PASIEN HIPERTENSI - Fatimah, Sitti; Hanifa, Hanina Liddini; Pratiwi, Bhekti (School of Pharmacy Institut Teknologi Bandung, 2025)
Hypertension is often referred to as a “silent killer” because it is typically not accompanied by clinical symptoms, yet it silently damages vital organs in the body. Medication adherence among patients influencing the success of hypertension therapy, and medication adherence is strongly affected by the level of patient knowledge. The purpose of this literature review to analyze the relationship between patient knowledge and medication adherence based on previous studies. This review was conducted by searching primary literature in the PubMed and Google Scholar databases, focusing on articles published within the last 15 years, using keywords such as hypertension, medication adherence, and knowledge level. The results showed that there were 14 articles demonstrated a positive correlation between the level of hypertension-related knowledge and patient’s medication adherence. However, medication adherence is influenced by several factors, including the patient's motivation for treatment, the role of healthcare professionals, the accessibility of healthcare services, and the complexity of the therapy. Therefore, interventions aimed at improve medication adherence should not be limited to enhancing patient knowledge alone. Additional improvements can be made by strengthening the role of healthcare professionals to build patient trust, improving healthcare service systems, and selecting treatments that are appropriate to the patient's condition.